Determination of velocity of layer of material is in hammer crusher (Modern Problems of Metallurgy, 2019)
Grinding workflows are used in various industries. Depending on the quality and properties of the material, the processing processes are carried out by a crushing machine of various designs. Impact crushers are widespread among them. For grinding fragile materials, with the formation of a product-air layer, hammer crushers are used. This is explained by the fact that the hammers reeling around the axes of the suspension change their relative speed, direction and depth of immersion in the product-air medium, which disrupts its uniform movement. The task of the study is to find the dependence of the average speed of a layer of comminuted material on the speed of hammers - one of the main parameters of a hammer crusher. The processes of breakage of fragile materials shallow are examined, with formation of product-air layer, by the crushers of shock action in that efficiency of destruction of particles depends mainly on their velocity in relation to hammers and immobile surface of working chamber. Theoretical studies are undertaken is a search of dependence of middle velocity of layer of the ground down material from velocity of hammers - one of basic parameters of hammer crusher. Dependences of middle velocity of layer of the ground down material are got on velocity of hammers of crusher that can be applied at determination of structurally-technological parameters of hammer crushers.
Keywords: blow; destruction; velocity